Pengaruh Budaya Organisasi dan Komitmen terhadap Kinerja Sekolah dengan Penerapan Sistem Informasi Akuntansi Sebagai Variabel Intervening di SMA Swasta Medan - Wahyuningrum, Retno; Sari, Eka Nurmala; Sari, Maya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine and analyze the influence of organizational culture and commitment to school performance by applying accounting information systems as an intervening variable in Medan Private High Schools. This type of research conducted in this study is to use a Quantitative Approach. The population in this study amounted to 196 Private High Schools in the city of Medan. The population used was all private high schools in the city of Medan with 392 respondents from the Principal and Treasurer. The number of samples in this study were 50 schools with the number of respondents 50 times 2, the total number of respondents was 100. The study of the independent variables studied was Organizational Culture and Commitment. In this study the independent variables studied were School Performance, and intervening variables were the application of accounting information systems. Data collection techniques in this study researchers used two ways, namely library research and field research. Data analysis technique used in this research is descriptive analysis, Structural Equation Modeling (SEM) Analysis based on Variance (Partial Least Square). The results of this study indicate that the variable Influence of organizational culture on school performance has a path coefficient of 0.143. The effect has a probability value (p-values) of 0.862> 0.05, meaning school performance has no effect in influencing organizational culture. The organizational culture variable on the application of accounting information systems has a path coefficient of 0.989 and has a probability value (p-values) of 0,000 <0.05, this shows that the influence of organizational culture on school performance is significant. commitment to school performance has a path coefficient of 0.406 and has a probability value (p-value) of 0,000 <0.05, this shows that commitment to school performance is influential. commitment to the application of accounting information systems has a path coefficient of -0.010 and has a probability value (p-values) of 0.658> 0.05, this shows that commitment has no effect on the application of accounting information systems and accounting information systems on school performance has a path coefficient - 0.415 and has a probability value (p-values) of 0.860> 0.05, this shows that the accounting information system is not significant in influencing school performance. Keywords: Organizational Culture, Competence, SIA and School Performance